واقع السياحة العلاجية في الجزائر و طموحاتها المستقبلية - ريوقي, سليمة (جامعة الوادي - University of Eloued, 2018)
السياحة العلاجية هي أهم أنواع السياحة، والتي لا تتوافق فيها المقومات مع العائدات، كونها تعتمد بنسبة 75% على خيرات الطبيعية كالمياه المعدنية، مكونات الرمال، مياه البحر، والطمي...الخ. ومن خلال ورقتنا هذه سوف نقف على واقع هذا النوع من السياحة في الجزائر كونها غنية بالثروات الطبيعية، لنختم مقالتنا هذه في الأخير بنتائج تظهر الواقع الحقيقي لهذا القطاع من خلال الأرقام المسجلة خلال الفترة المدروسة(2012 – 2016). Summary: Medical tourism is the most important type of tourism, which does not correspond to the components with the proceeds, being dependent on 75% of natural resources such as mineral water, components of sand, sea water, silt ... etc. We will focus on the reality of this type of tourism in Algeria as it is rich in natural resources. Finally, we conclude with the results that show the true reality of this sector through the figures recorded during the period studied (2012-2016).
The reality of medical tourism in Algeria and its future ambitions
مقال
Keywords: السياحة؛ المقومات الطبيعية؛ السياحة العلاجية؛ الحمامات المعدنية؛ الاستثمار السياحي. .